Peer Feedback as a Tool to Enhance EFL Learners’ Writing Skills: A Case of First-Year EFL Learners at the University of Amar Telidji − Laghouat - Bouchenak, Salima; Gasmi,mustapha (Faculty of Letters and Foreign Languages Department of English, 2025)
The present research attempts to investigate the effectiveness of peer feedback in developing EFL writing skills of 1st year EFL and translation students in the English and translation department at the University of Amar Telidji in Laghouat. Moreover, the study aims to determine whether the repeated engagement in giving and receiving peer feedback impacts the development of the writing skills. This study also seeks to highlight the main challenges EFL learners may face when providing and receiving peer feedback and the strategies that can be implemented to improve the effectiveness of peer feedback in EFL writing classes. Therefore, in order to reach the aim of this study, descriptive analytical method and quantitative approach were adopted to collect and analyze accurate data. A questionnaire has been administered to 80 first-year EFL and translation students at the department of English and translation, University of Laghouat. The findings of the questionnaire confirmed the hypothesis that the repeated engagement in peer feedback improves the writing accuracy and develops the critical thinking of learners through collaborative learning. Furthermore, some challenges EFL learners may face when providing and receiving peer feedback such as preferring teacher‟s feedback and the lack of experience. In addition, the results also revealed that peer feedback can be implemented by teaching the learners how to provide insightful feedback and receive feedback with receptiveness. Accordingly, the results of this study are important for English language learning, especially for English as foreign language learners; it highlights the importance of implementing peer feedback in EFL classes to increase learners‟ writing skills